2020
DOI: 10.1177/2150132720953723
|View full text |Cite
|
Sign up to set email alerts
|

Building Capacity for Medication Assisted Treatment in Rural Primary Care Practices: The IT MATTTRs Practice Team Training

Abstract: Objectives: In response to rural communities and practice concerns related to opioid use disorder (OUD), the Implementing Technology and Medication Assisted Treatment Team Training in Rural Colorado study (IT MATTTRs) developed a training intervention for full primary care practice (PCP) teams in MAT for OUD. This evaluation reports on training implementation, participant satisfaction, and impact on perceived ability to deliver MAT. Methods: PCPs in the High Plains Research Network and Colorado Research Networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Across roles, participants reported high levels of satisfaction and significantly higher self-rated ability to deliver treatment components after the training. 18 Third, practices implemented many of the processes and components necessary for delivering treatment. Across participating practices, treatment components implemented significantly increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Across roles, participants reported high levels of satisfaction and significantly higher self-rated ability to deliver treatment components after the training. 18 Third, practices implemented many of the processes and components necessary for delivering treatment. Across participating practices, treatment components implemented significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in the HPRN The IT MATTTRs Practice Team Training was developed by the research team, local medication-assisted treatment experts, community members, and professional practice facilitators. 18 Based on the American Society of Addiction Medicine and Center for Disease Control and Prevention guidelines, the training covered the epidemiology of OUD, pharmacology of buprenorphine, neurobiology of addiction, and detailed treatment steps. The training included facilitated discussion among office staff, nurses, medical assistants, clinicians, and billing and coding staff to encourage the identification of existing resources on which to build and guide implementation.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we identified 58 opioid jargon used in the anonymous marketplaces and forums (Table 2). Combining opioid jargon with known opioid product names [25][26][27], we generated an opioid keyword data set consisting of 311 opioid keywords with 13 categories. We manually validated all keywords and the corresponding categories to guarantee their correctness.…”
Section: Opioid Jargon Identificationmentioning
confidence: 99%
“…The study used a multilevel approach that included training for primary care practice teams to build capacity to provide MAT for OUD and support for clinicians to become waivered to prescribe buprenorphine for OUD. The results of those study activities will be reported elsewhere 12 . Another component of IT MATTTRs was the development of 2 community interventions to change the local conversation about OUD and MAT.…”
Section: Purposementioning
confidence: 99%
“…The results of those study activities will be reported elsewhere. 12 Another component of IT MATTTRs was the development of 2 community interventions to change the local conversation about OUD and MAT. This manuscript describes the development and implementation of the community‐based interventions created by rural community members and researchers and explores change in knowledge, attitudes, and beliefs related to OUD and MAT in community members living in a rural and frontier agricultural region.…”
Section: Purposementioning
confidence: 99%